InGaN stress compensation layers in InGaN/GaN blue LEDs with step graded electron injectors. (April 2018) - Sheremet, V.; Gheshlaghi, N.; Sözen, M.; Elçi, M.; Sheremet, N.; Aydınlı, A.; Altuntaş, I.; Ding, K.; Avrutin, V.; Özgür, Ü.; Morkoç, H.
Abstract: We investigate the effect of InGaN stress compensation layer on the properties of light emitting diodes based on InGaN/GaN multiple quantum well (MQW) structures with step-graded electron injectors. Insertion of an InGaN stress compensation layer between n-GaN and the step graded electron injector provides, among others, strain reduction in the MQW region and as a result improves epitaxial quality that can be observed by 15-fold decrease of V-pit density. We observed more uniform distribution of In between quantum wells in MQW region from results of electro- and photoluminescence measurement. These structural improvements lead to increasing of radiant intensity by a factor of 1.7–2.0 and enhancement of LED efficiency by 40%. Highlights: InGaN step-graded electron injector prevent electron overflow by its cooling. InGaN stress compensation layer provides strain reduction in the MQW and SGEI. SCL allow to get uniform distribution of In in different QWs of LED. SCL results in enhancement of radiant intensity and LED efficiency.